Raising awareness of environmental risks : a case study in Portugal - Pinto, Lígia (2004)
This paper presents a study of the effects of an abandoned mining site on the environment and human health and discusses possible mechanisms to raise public awareness of the risks posed by mining sites, and environmental risks in general. The case study reported concerns the Campo de Jales mining site located in the northern part of Portugal, which is currently being sealed. The action taken and outlined in this paper is based on the lines of action established by the Sixth Environmental Action Programme.